THE EFFECT OF STRATIFIED DOSES OF CURRY LEAF EXTRACT (MURRAYA KOENIGII) ON TOTAL CHOLESTEROL AND TRIGLYCERIDES IN MALE SPRAGUE-DAWLEY RATS INDUCED BY HIGH FAT FEED - Muhammad Iqbal Reynaldi; Santoso Santoso; Kusmiyati Tjahjono (Jurnal Kedokteran Diponegoro, 2021)
Background: High level of total cholesterol and tryglicerides in the blood can cause atherosclerosis. Curry leaves are often used by the society to reduce total cholesterol and trygliceride levels in the blood, but no studies have examinded the effective dosage of curry leaf extract to reduce total cholesterol and triglyceride levels.